Radiation Disinfestation of Honeybee Combs Infested with Greater Wax Moth Eggs - Mansour, Mohammed (Journal of Apicultural Science, 2020)
The sensitivity of different developmental stages of greater wax moth ( L.) eggs to gamma irradiation was examined. Eggs, 25 to 144 h-old, were exposed at 48 h intervals to gamma radiation dosages (50 to 400 Gy), and the effects on egg hatch, pupation and adult emergence were investigated. The developmental rate of irradiated-egg larvae and pupae to adult stage was also studied. Results showed that the irradiation sensitivity of eggs decreased with increased age of the eggs when irradiated. In 25–48 h-old eggs, 50 Gy dose significantly reduced egg hatch and at 200 Gy dose no egg hatch was observed. Eggs 73–96 h-old were slightly more tolerant to irradiation treatment; hatching completely ceased at 250 Gy dose. Sensitivity to gamma irradiation reached its lowest level however when 121–144 h-old eggs (few h. before egg hatch) were irradiated. 350 Gy dose reduced egg hatch to about 3%, and at 400 Gy no egg hatch was noted. Survival to the adult stage was also negatively affected. At the most radio-tolerant stage (121–144 h-old), 100 Gy dose significantly reduced larval survival to the adult stage and 300 Gy completely prevented it. The development rate of larvae and pupae resulting from irradiated eggs was also negatively affected.